THE EFFECTIVENESS OF USING “PORTO FOLIO” IN TEACHING AND LEARNING PROCESS - Ima Chusnul Chotimah (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2015)
This research focused on the use of portofolio as the strategy of the teaching and learning process. The resercher limited on one typical of portofolio used in this research, namely summarizing. However, it was found that most of the learning process in STKIP PGRI Jombang used group presentation. It was also done by the researcher in Belajar Pembelajaran subject. The researcher would like to apply the use of portofolio in group presentation. To investigate the effectiveness of the strategy used , the writer conducted a quasi-experimental research design which there were two groups, experimental group and control group. The subject of  the research was 37 students of 2014 A as the experimental group and 31 students of 2014 B as the control group. In collecting the data, the researcher gave posttest to both groups. In which the experimental group used portofolio in the treatment. After having the data, then the researcher analyzed it by using ANCOVA. And the result shows that the significant value is higher than significant level (0,429 > 0.05). It means that the use of portofolio does not have significant effect applied in teaching and learning process.